A simple high performance liquid chromatography–mass spectrometry method for Therapeutic Drug Monitoring of isavuconazole and four other antifungal drugs in human plasma samples - Fatiguso, Giovanna; Favata, Fabio; Zedda, Ilaria; De Nicolò, Amedeo; Cusato, Jessica; Avataneo, Valeria; Di Perri, Giovanni; D’Avolio, Antonio (Journal of pharmaceutical and biomedical analysis, 2017)
Overlaid chromatograms showing the retention times of Fluconazole (FLU), Voriconazole (VRC), Posaconazole (PSC), Isavuconazole (ISC), Itraconazole (ITC) and their corresponding internal standards in a calibration standard sample. [Display omitted] •Simple HPLC–MS method to quantify 5 antifungal triazoles in human plasma.•Fast protein precipitation protocol, ideal for clinical routine use.•Full validation following FDA and EMA guidelines.•High expected applicability, due to wide use of TDM in antifungal treatments. Triazoles chanced the prevention and treatment of invasive fungal infections, but their pharmacokinetic properties are still unclear. In particular, isavuconazole (ISC) is a new broad-spectrum antifungal triazole approved in 2015 as first-line treatment for intravenous and oral use against invasive aspergillosis and for mucormycosis. Nowadays, the optimal management of the treatments with triazoles requires the use of Therapeutic Drug Monitoring (TDM), in order to prevent sub-therapeutic or toxic concentrations. In turn, the routine use of TDM requires reliable quantification methods The aim of this work was the development and full validation of a HPLC-mass spectrometry assay for the simultaneous quantification of fluconazole, itraconazole, isavuconazole, posaconazole and voriconazole in human samples. Both standards and quality controls were prepared in human plasma. After the addition of internal standard (6,7-dimethyl-2,3-di(2-pyridyl)quinaxoline for voriconazole, posaconazole and itraconazole; stable isotope labeled compounds for fluconazole and isavuconazole), protein precipitation with acetonitrile and dilution with water were performed. Chromatographic separation was performed on Atlantis® T3 5μm 4.6×150mm column, with a gradient of water and acetonitrile, both added with 0.05% formic acid. Accuracy, intra-day and inter-day imprecision fitted FDA and EMA guidelines, while matrix effects and recoveries resulted stable between samples for each analyte. Stability results were in accordance with previously published data. Finally, we tested this method by monitoring plasma concentrations in real patients and using external quality controls with good results. This method resulted very simple, fast, cheap and very useful for TDM application, to improve clinical management of antifungal therapy in critically ill patients.